SUPPLY CHAIN RISK MANAGEMENT OF FISH FEED PT. NEW HOPE AQUAFEED INDONESIASUPPLY CHAIN RISK MANAGEMENT FISH FEED OF PT. NEW HOPE AQUAFEED INDONESIA - Muhammad Yusril Aditya Mas’ud; Wiludjeng Roessali; Komalawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
PT New Hope Aquafeed Indonesia, a subsidiary of the New Hope Group, is implementing an agile supply chain model that combines efficient mass production of commercial fish feed with the ability to respond to specialized market demands. This model was chosen to deal with challenges such as raw material price fluctuations, seasonal demand and logistics. Supply chain flow mechanisms were identified based on six key dimensions: production, finance, information, logistics, supply and demand, and risk and resilience flows. Risk identification using the SCOR 11.0 model resulted in 47 risk events, with the highest number of risks in the Deliver process (21%). Risk impact analysis using FMEA showed that there were 6 prioritized risks categorized as very high risk, with the highest risk being inappropriate ingredient nutritional specifications (RPN 720). The main risk factors include inappropriate nutritional specifications of raw materials, inaccurate forecasting, feed formulation determination, raw material substitution, feed quality deviation, and distribution price increase during the holidays. These risks affect feed prices, farmer confidence and the sustainability of aquaculture production. Risk mitigation strategies were developed using the 5W+1H approach based on the highest RPN values. Mitigation recommendations include quality improvement, supply chain management, production planning, distribution systems, as well as improving the capabilities of human resources and systems.